Strategi Pemasaran Kue Rumahan Di Timur Indah 5 Kota Bengkulu - Ramdhani, Heru (Universitas Dehasen Bengkulu, 2024)
A home-based business is any type of business that can be run at home. Business operations are carried out at home, such as marketing products, buying and selling transactions, storing inventory, and others. Therefore, a community service program with the title